Campo 6, The Spiral Village - Peeters, Tom (Maastricht : Bonnefantenmuseum, 1997)
Aitken, Doug ; Cattelan, Maurizio ; Chapman, Dinos & Jake ; Ciraci, Sarah ; Demand, Thomas ; Dion, Mark ; Gabellone, Giuseppe ; Kentridge, William ; Moffatt, Tracey ; Orozco, Gabriel ; Parreno, Philippe ; Pippin, Steven ; Rehberger, Tobias ; Taylor-Wood, Sam ; Tayou, Pascale Marthine ; Tiravanija, Rirkrit ; Debaere, Hugo ; Muybridge, Eadweard ; Andre, Carl
biografie
Campo 6, The Spiral Village, Bonnefantenmuseum, Maastricht, 26.1. - 25.5.1997
Nederlands
boek